ANALYSIS EMPLOYEE JOB SATISFACTION TOWARD EMPLOYEE WORK MOTIVATION AT PELAKSANA HARIAN BADAN NARKOTIKA NASIONAL NORTH MINAHASA REGENCY - Tiwang, Riadiani Anastasia; Tielung, Maria V. J. (FEB Universitas Sam Ratulangi Manado, 2015)
In order to create a smooth and can produce good work motivation, it is necessary to increase job satisfaction for employees. The success of the company is required to perform optimally in a positive attitude towards work, which in turn can generate a good motivation. The purpose of this study was to determine the effect of job satisfaction on work motivation. Where researchers study took place at the Daily Executive Office of the Badan Narkotika Nasional (BNN) North Minahasa Regency, with 9 employees as informants and using purposive sampling method. The method used to analyze the research is qualitative method. The results showed employee satisfaction has a significant influence on employee motivation either simultaneously or partially. Daily Executive Office Manager BNN North Minahasa Regency expected more attention to what might motivate employees so that they are satisfied on the job. If employees can be satisfied that they are motivated to perform the job well. Keywords: job satisfaction, work motivation, performance, organization